PENGARUH PACKAGING DAN PROMOSI DENGAN MINAT BELI TERHADAP KEPUTUSAN PEMBELI DI NYAH LIEM HERBAL FARM KABUPATEN KENDAL - Faiz Maulana Majid; Ratih Hesty Utami Puspitasari; Shofif Sobaruddin Akbar (Jurnal Ilmiah Manajemen dan Akuntansi, 2026)
This study aims to analyze the influence of packaging and promotion along with purchase intention on buying decisions at Nyah Liem Herbal Farm in Kendal Regency. It is based on the idea that purchasing decisions for a product are influenced by several factors, including the product itself, promotion, packaging, and marketing strategy. This research focuses on examining purchase intention and buying decisions for Nyah Liem Herbal feed concentrate products made from herbal ingredients. This study uses quantitative research, which is causal or associative in nature. The sampling technique used is total sampling of all consumers who purchased Nyah Liem Herbal concentrate products, totaling 38 people. Data collection in this study was carried out using a questionnaire. Data analysis employed instrument testing, prerequisite testing, and hypothesis testing with the help of the SmartPLS application. The research results show a Goodness of Fit index value of 0.698, which is higher than the normative value of 0.36, indicating that the GoF value is considered large. The percentage of the questionnaire items used shows an R-Square value for the variables of packaging and promotion on buyer decisions of 48%. Packaging and promotion on purchase intention is 92.7%. The model has an average effect size of 0.226, indicating that the model has an effect size categorized as medium or moderate. The conclusions are: (1) there is an influence of packaging and promotion on purchase intention and buyer decisions, (2) there is no significant influence of purchase intention on buyer decisions, (3) purchase intention cannot mediate the influence of promotion and packaging on buyer decisions for consumers of Nyah Liem Herbal Farm livestock concentrate products in Kendal Regency. For future researchers, it is hoped that subsequent research will add several factors that affect buyer decisions.